The Effect of Applying Talking Stick Type Learning Model in Mufrodat Learning: Quasi Experimental Research on Junior High School - Ihda Filzafatin Habibah; Munirul Abidin (Sustainable, 2023)
This study aims to determine the effect of the application of the "Talking Stick" type learning model on improving Mufrodat (Arabic Vocabulary) learning in junior high school students. In this study, researchers used research based on Quasi-Experimental studies by dividing students into two classes, namely the experimental class and the control class. This research is based on several complex problems, namely Arabic learning is still considered as one of the difficult and boring subjects. The results showed that by using the "Talking stick" type of learning model, mufrodat learning in students increased compared to applying the conventional learning model to generally. With this research, it is expected to be a motivation for educators at every level of education to continue and continue to innovate in every application of learning by Models that vary and adapt to the technology of the era that exists today.